Ang batang nangarap ng kapayapaan (The child who dreams of peace) - Papasin, Bimbo; Sarmiento, Jan; Papasin, Odie (Quezon City Katha Publishing Co., Inc., 2009)
"Mindanao was once a quiet and peaceful land where many valiant and ingenious Filipinos are born. Every respects the belief of his/her fellow being. In the blink of an eyes, sadness and chaos ruled the land. What can a child like Aliyah achieve to bring back peace in her native land. Find out in this story the hardships and the sacrifices of a Muslim child who dreamt of peace that she had yearned for do long."
Text in English and Filipino.
Keywords: Muslims -- Philippines -- Mindanao -- History; Peace -- Juvenile fiction